2016
DOI: 10.1002/bmc.3882
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase produced from Aspergillus sp. (UCP 1276) using chicken feather industrial residue

Abstract: An extracellular collagenolytic serine protease was purified from Aspergillus sp., isolated from the Caatinga biome in northeast Brazil by a two-step chromatographic procedure, using an anion-exchanger and gel filtration. The enzyme was produced by submerged fermentation of feather residue as a substrate. The purified collagenase showed a 2.09-fold increase in specific activity and 22.85% yield. The enzyme was a monomeric protein with a molecular mass of 28.7 kDa, estimated by an SDS-PAGE and AKTA system. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Numerous recent studies on fungal proteases have revealed them to be acidic or alkaline rather than neutral proteases; widely reported examples include the acid protease from Aspergillus oryzae HG76 (Li et al 2014 ), A. flavus (Franco et al 2017 ) and A. foetidus (Souza et al 2015 ), with alkaline protease noted in Aspergillus sp. UCP 1276 (Ferreira et al 2016 ), A. terreus (Biaggio et al 2016 ), and Rhizopus oryzae (Mushtaq et al 2015 ). Currently, the important focus for industrial application is to find a neutral protease derived from fungi that offers good thermal stability, acid–alkali resistance and a high affinity to protein.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous recent studies on fungal proteases have revealed them to be acidic or alkaline rather than neutral proteases; widely reported examples include the acid protease from Aspergillus oryzae HG76 (Li et al 2014 ), A. flavus (Franco et al 2017 ) and A. foetidus (Souza et al 2015 ), with alkaline protease noted in Aspergillus sp. UCP 1276 (Ferreira et al 2016 ), A. terreus (Biaggio et al 2016 ), and Rhizopus oryzae (Mushtaq et al 2015 ). Currently, the important focus for industrial application is to find a neutral protease derived from fungi that offers good thermal stability, acid–alkali resistance and a high affinity to protein.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the example above, when an enantiomer of a useful substance exists under development, it should be verified that there is a difference in activity depending on each form. Although studies on the anti-cancer activity of ginsenoside Rh2 have been performed on lung, breast, liver, colorectal cancers, and leukemia, there has been no study of the cellular pattern of cancer cells when Rh2 was treated in real-time (Ge, Yan, & Cai, 2017;Han et al, 2016;Kim & Choi, 2016;Li, Li, Dong, Wang, & Li, 2017;Ren, Shi, Teng, & Yao, 2018;Wan et al, 2017). Among the existing studies, there is a study on how Rh2 using HCT-116 cells can act as a specific mechanism of anti-cancer activity for a colorectal cell line (Han et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The method used for enzyme extraction was previously described by Ferreira et al []. In brief, after using anionic chromatography on DEAE‐sephadex, for the gel filtration method, an ÄKTA Avant purifier (GE Healthcare, Uppsala, Sweden) was used to separate the protein fractions eluted by Tris–HCl buffer (pH 8) added by 0.15 M NaCl on a Superdex 75 (HR10/300GL) PC 3.2/30 column (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%